What Can We Learn from Business Innovation Fail-ure of Uber in Southeast Asia Market? - Ismail Khozen; Illona Setianty; Farah Dina Meiriza (Politeknik Negeri Bengkalis, 2021)
Uber is a global pioneer in the sharing economy platform entitled ride-hailing. It started to enter the Asian market in 2013-2014 with various community responses in each region. In March 2018, Uber withdrew from the competition in Southeast Asia after being acquired by one of the dominant players in the region, Grab. In connection with Uber's failure to operate its business in the region, this paper discusses Uber's business model, business expansion, competition in the market, and the factors that led to Uber's failure in the Southeast Asian market. To comprehensively describe the developing context, we used a qualitative method with a systematic data collection approach from literature reviews in conducting this study. This study emphasizes that large funding supports do not guarantee the success of business operations in a more globalized setting. Different market characteristics require different approaches. The case of Uber's failure in the Southeast Asian market, even though it was supported by large funds to